Observation of intra- and intermolecular vibrational coherences of the aqueous tryptophan radical induced by photodetachment - Muhammad Shafiq Mohd Yusof (2021)
The study of the photodetachment of amino acids in aqueous solution is pertinent to the understanding of elementary processes that follow the interaction of ionizing radiation with biological matter. In the case of tryptophan, the tryptophan radical that is produced by electron ejection also plays an important role in numerous redox reactions in biology, although studies of its ultrafast molecular dynamics are limited. Here, we employ femtosecond optical pump-probe spectroscopy to elucidate the ultrafast structural rearrangement dynamics that accompany the photodetachment of the aqueous tryptophan anion by intense, ∼5-fs laser pulses. The observed vibrational wave packet dynamics, in conjunction with density functional theory calculations, identify the vibrational modes of the tryptophan radical, which participate in structural rearrangement upon photodetachment. Aside from intramolecular vibrational modes, our results also point to the involvement of intermolecular modes that drive solvent reorganization about the N-H moiety of the indole sidechain. Our study offers new insight into the ultrafast molecular dynamics of ionized biomolecules and suggests that the present experimental approach can be extended to investigate the photoionization- or photodetachment-induced structural dynamics of larger biomolecules.